Different mean thickness implicates involvement of the cortex in migraine. Issue 37 (September 2016) - Yu, Zhi-bo; Peng, Jing; Lv, Yan-bing; Zhao, Ming; Xie, Bing; Liang, Ming-long; Li, Hai-tao; Zhou, Zhen-hua
Abstract : Abstract: The results of neuroimaging studies on migraines have shown that the functions and functional connectivity networks of some brain regions are altered in migraine patients, and different brain structure volumes have also been observed in recent years. However, it is still not known whether the mean thickness of the cortex is different in migraine patients. A total of 48 migraine without aura (MWoA) patients in interictal phase and 48 healthy controls were enrolled in this study. All subjects received neurological and magnetic resonance imaging (MRI) examinations. Automatic segmentation processing of high-resolution MRI structure images was performed using FreeSurfer software. The mean cortical thickness of many brain regions in the frontal lobe, temporal lobe, occipital lobe, parietal lobe, and insula in the migraine patient group was significantly decreased compared with that in the healthy control group. The mean cortical thickness of the insula anterior was positively correlated with the duration of the disease course, while the mean cortical thickness of insula superior and insula inferior was negatively correlated with the duration of the disease course. The results showed that MWoA results from a complex interactive reaction involving many brain regions and many brain network systems together. However, it is still not clear whether the difference in the brain structure of migraine patients is the result or the cause of headache, which is a topic that must be better elucidated. Therefore, longitudinal neuroimaging studies on migraine patients with large samples sizes should be performed using more advanced neuroimaging techniques.